Enhancing informed consent through multimedia tools in pediatric spinal surgery: a comprehensive review - Rosa Filezio, Marina; Sharma, Nishan; Thull-Freedman, Jennifer; Ferri-de-Barros, Fabio; Santana, Maria J. (Frontiers in Pediatrics, 2024)
Pediatric spine surgery is a high complexity procedure that can carry risks ranging from pain to neurological damage, and even death. This comprehensive mini review explores current best practice obtaining valid and meaningful informed consent (IC) prior to pediatric spinal surgery, including modalities that support effective comprehension and understanding. An evaluation of the literature was performed to explore understanding of surgical IC by patients or their guardians and the role of multimedia tools as a possible facilitator. The evidence discussed throughout this review, based on legal and ethical perspectives, reveals challenges faced by patients and guardians in achieving comprehension and understanding, especially when facing stressful medical situations. In this context, the introduction of multimedia tools emerges as a patient-centered strategy to help improve comprehension and decrease pre-operative uncertainty. This review highlights the need for a tailored approach in obtaining IC for pediatric patients and suggests a potential role of shared decision-making (SDM) in the surgical discussion process.